2001
DOI: 10.2337/diabetes.50.4.797
|View full text |Cite
|
Sign up to set email alerts
|

The Novel Imidazoline Compound BL11282 Potentiates Glucose-Induced Insulin Secretion in Pancreatic β-Cells in the Absence of Modulation of KATP Channel Activity

Abstract: The insulinotropic activity of the novel imidazoline compound BL11282 was investigated. Intravenous administration of BL11282 (0.3 mg ⅐ kg -1 ⅐ min -1 ) to anesthetized rats did not change blood glucose and insulin levels under basal conditions, but produced a higher increase in blood insulin levels and a faster glucose removal from the blood after glucose infusion. Similarly, in isolated Wistar rat pancreatic islets, 0.1-100 mol/l BL11282 potently stimulated glucose-induced insulin secretion but did not modul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
39
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 18 publications
4
39
0
Order By: Relevance
“…One guanidinium compound with insulinotropic property (BTS 67 582) was explored as an oral antidiabetic agent, assuming that it acts as an imidazoline analogue [20,34,35]. On the other hand, several imidazoline compounds have been synthesised recently that do not inhibit K ATP channel activity, but nevertheless stimulate insulin secretion [36,37]. Whether the insulinotropic effect of these second-generation imidazolines [38] is simply due to the K ATP channel-independent mechanism of the conventional imidazolines [17,38] or represents something new is unclear thus far.…”
Section: Discussionmentioning
confidence: 99%
“…One guanidinium compound with insulinotropic property (BTS 67 582) was explored as an oral antidiabetic agent, assuming that it acts as an imidazoline analogue [20,34,35]. On the other hand, several imidazoline compounds have been synthesised recently that do not inhibit K ATP channel activity, but nevertheless stimulate insulin secretion [36,37]. Whether the insulinotropic effect of these second-generation imidazolines [38] is simply due to the K ATP channel-independent mechanism of the conventional imidazolines [17,38] or represents something new is unclear thus far.…”
Section: Discussionmentioning
confidence: 99%
“…3) raises the possibility of developing Kv channel based therapeutics. The enormous interest in potential glucosedependent therapeutics is evidenced by current research into glucose-dependent secretagogues such as the incretin hormones glucagon-like peptide-1 (GLP-1) and gastric inhibitory polypeptide (GIP) and their analogues [68], the imidazoline compounds [69,70], and agonists of the protein kinase A (PKA) signalling pathway [71]. The theory behind the glucose-dependence of Kv channel antagonists is quite simple.…”
mentioning
confidence: 99%
“…Similarly, others have shown that imidazoline substances increased insulin release after irreversible blockade or downregulation of ␣ 2 -adrenoceptors, and they proposed that the stimulatory effect of the compounds on insulin release was probably related to their imidazoline moiety (15-17). Importantly, some imidazoline compounds exerted a strong effect on the exocytotic component of the insulinotropic effect of glucose (8,18). Furthermore, several imidazolines have already shown promising antihyperglycemic effects in animal models of diabetes and in human subjects (19 -21).…”
mentioning
confidence: 99%
“…However, the necessity of injecting this peptide during the treatment led to the idea to search for small organic compounds possessing glucose-dependent insulinotropic activity similar to GLP-1. Among those compounds, of special interest are novel imidazoline compounds (8,9).…”
mentioning
confidence: 99%